Study of scan protocol for exposure reduction in hybrid spectral micro‐CT. Issue 4 (6th March 2014) - Opie, Alex M. T.; Bennett, James R.; Walsh, Michael; Rajendran, Kishore; Yu, Hengyong; Xu, Qiong; Butler, Anthony; Butler, Philip; Cao, Guohua; Mohs, Aaron M.; Wang, Ge
Summary The hybrid spectral micro‐computed tomography (CT) architecture integrates a conventional imaging chain and an interior spectral imaging chain, and has been proven to be an important development in spectral CT. The motivation for this study is to minimize X‐ray exposure for hybrid spectral micro‐CT using both simulated and experimental scan data while maintaining the spectral fidelity of the reconstruction. Three elements of the hybrid scan protocol are investigated: truncation of the interior spectral chain and the numbers of projections for each of the global and interior imaging chains. The effect of these elements is quantified by analyzing how each affects the reconstructed spectral accuracy. The results demonstrate that there is significant scope for reduction of radiation exposure in the hybrid scan protocol. It appears decreasing the number of conventional projections offers the most potential for exposure reduction, while further reduction is possible by decreasing the interior FOV and number of spectral projections. SCANNING 36:444–455, 2014. © 2014 Wiley Periodicals, Inc.